PENGATURAN TANGGUNG JAWAB NOTARIS AKIBAT PEMALSUAN KETERANGAN DI DALAM AKTA YANG DIBUATNYA - Arianty, Siti Saza'a (Universitas Sriwijaya, 2017)
Notaries as public officials have full responsibility towards the construction of Authentic Deed. This regulation is arranged in Law Number 2 2014 about the amendment of Law Number 30 2004 about the position of Notaries. However, in the real situation, whether it is caused by less knowledge, circumspection or fairness from Notaries in constructing a deed, it causes counterfeiting information which also causes disadvantages to the parties concerned. Therefore, the main legal issue raised in this study was the regulation of Notaries’ responsibility as the results of counterfeiting information in the deed that they made, with some legal sub-issues which were the question of whether the law has been set on Notaries’ responsibility who had forged statements and how the legal protection for the parties as a result of Notaries who falsified information in the deed that they made.Through prescriptive research, with laws approaching, conceptual, cases and legal histories, then performed identification and systematization steps on legal materials and then it was analyzed to get the conclusion. The results showed that the regulation of Notaries’ responsibility due to counterfeiting information in the deed that they made was not set entirely in the Laws of Notaries’ position and the Conduct Code of Notaries, however the Notaries could be accountable his deed civilly based on acts against the law in Article 1365 of Civil Laws, and could be accountable criminally regarding counterfeiting information which is arranged in Article 263, Article 264 and Article 266 in the Book of Criminal Laws. It included the setting up of legal protection for the parties concerned due to counterfeiting description in the deed that Notaries made, and also it was not particularly set in the Laws of Notaries’ position. The setting of Notaries’ responsibility due to counterfeiting information in the deed that they made should be arranged clearly in the future, including imposing sanctions for violations committed by Notaries due to counterfeiting information.